Pengaruh Kepemilikan Institusional, Leverage Dan Ukuran Dewan Komisaris Terhadap Pengungkapan Corporate Social Responsibility (Csr) Dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Husniatus Zahroh; Hartono Hartono; Nur Ainiyah; Tatas Ridho Nugroho (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to examine the effect of Ownership Institutional, Leverage, and Size Board Commissioner on CSR disclosure with Company Size as variable moderation. Population in this study is company Mining listed on the Indonesia Stock Exchange in 2019-2022, Samples obtained as many as 48 of 12 companies, taking sample use technique Purposive Sampling. Data used on study This is secondary data. Data analysis study this using an alternative structural equation modeling (SEM) using SmartPLS. The results of this study show Size Board Commissioner have a positive significant on CSR disclosure with level significant of 0,041<0,05. Institutional Ownership and Leverage have no effect on CSR disclosure. Company size cannot moderate Institutional Ownership, Leverage and Board of Commissioners Size on CSR disclosure.